STRATEGI PENGEMBANGAN USAHA KECIL MENENGAH UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT (STUDI KASUS SENTRA PRODUKSI PENGELASAN DI GETAP) - heni ariyani; Halpiah Halpiah (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2020)
This research is entitled "The Strategy of Small and Medium Enterprises to Increase Society Revenue (Case Study of Center for Elimination in Getap)". The purpose of this thesis is to find out the size of the income generated from the Welding in Getap, Cakra Selatan Baru Village, Cakranegara District, knowing what things affecting income, production costs, the quality of the products produced and the ways of marketing.The type of research used in this study is qualitative research with a descriptive approach by utilizing interview activities and direct observation as a technique of data collection, informants from this study consisted of the Welding Owners, Employees and Communities in Getap, South Cakra, New Cakranegara District.The results of this study indicate that the income of the welding is quite large on average - Rp. 20,000,000 per month which also undermines unemployment because workers who work in, work hard and want to take part in training conducted by the government so that they have expertise in the field of welding. On the other hand, with the presence of the welding, it was able to improve the living standards of the people around Getap with the opening of small kiosks of snack vendors, and rice stalls which earned an average daily income of Rp.250,000 to Rp.300,000 perday.